Inservice Training Implementasi Pembelajaran Daring Bagi Pendidik - Susilawati Susilawati; Rian Vebrianto; Musa Thahir; Mery Berlian; Radeswandri Radeswandri (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service activity aims to provide teachers with skills in improving understanding and skills in implementing online learning. The problems faced include those related to learning at school which is done online and this makes it difficult for those who have not done it before. The implementation method used in solving these problems begins with the socialization stage, participant recruitment, implementation of service and assistance, monitoring and evaluation. The socialization stage is carried out through survey methods and interviews at the service location. Next, the team determined the solutions and things needed by SMAN 1 Ujung Batau. At the implementation stage, participants are invited to actively participate in direct involvement in gaining experience in providing quality learning media during the pandemic, and how to develop online learning procedures. This activity resulted in being able to help SMAN 1 Ujung Batu in improving the ability of SMAN teachers in Ujung Batu to be able to implement online learning. However, the participants were still relatively unfamiliar in using some software/software to support online learning.